Onset of natal dispersal in Peregrine Falcon from Mediterranean islands (Italy) - Bond, Salvatore; Guzzo, Enrico; Mascara, Rosario; Sarà, Maurizio (Ornis Hungarica, 2018)
Basic information on natal dispersal of Peregrine Falcons is virtually lacking in Europe, despite increased attention on this species, and the sensitivity of this stage in the Peregrines’ life history. In this study, we collected satellite telemetry data during the onset of natal dispersal of 19 Peregrine Falcons tagged in Sicily and the Aeolian archipelago (Italy). We divided the onset of dispersal into the following 3 periods: post-fledging dependence period (PFDP), wandering, and wintering. PFDP lasted on average 47±16 days, during which young peregrines moved very little (0.167 km), and explored small areas (0.226 km2) far from the nest cliff, and showed no sex differences. The wandering phase was highly individualistic, with median net displacements of 23.97 km. Both PFDP and wandering bearings were oriented towards NNE-ESE. Only five individuals went sporadically outside the island borders. During their first winter, Peregrines had a mean home range of 135.65±82.31 km2 spatially scattered across Sicily and mainly composed of open habitats, like cereal steppes, arboreal crops and agri-mosaics. Individuals had a dissimilar assortment in habitat composition, however the urban habitat was the most selected and the woodland the least. At night, during both wandering and wintering phases Peregrines used rocks, cliffs and electricity pylons in frequencies not statistically different between sex, phase and type of roost. Only two individuals had significant use of pylons and one of rocks. The multifaceted framework of Peregrine Falcon’s natal dispersal was described here for the first time in a Mediterranean population.